A CASE STUDY OF CULTURAL FESTIVAL SAMYAK MAHADAN FESTIVAL AT NAGBAHAL, PATAN, NEPAL - Shrestha, Manita; BHANDARI, NEHA (Journal of the Asia Ethno-Forms Association, 2022)
＜Introduction＞One Newar tradition related festival of the monastery is the Itilhane Samyak Mahadana, which is also known as Dipankara Parva, observed once in every five years. This festival is an outstanding practice of charity. During the festival large images of Buddhist goddess (Dipankara Buddha, Avalokitesvra, Basundhara, Arya tara) display at Nagbahal, and offerings are made to goddess by Shakya and Bajracharya monks as per the Newar tradition, which is the main attraction of the festival. The festival brings across widespread Newar people with any occupation and races together to celebrate being one.Literally, Samyak means to perform the art of charity in an unconditional manner with a clear mind. There is mention of three types of Bodhijnana in Buddhist text that is Sravaka Bodhi, Pratyeka Bodhi and Samyak Bodhi. Among these, “Samyak” represents absoluteness and “Bodhi” characterizes the supreme knowledge of Buddhist. Hence, the festival is a path of a Bodhisattva that leads toward the attainment of Samyak Sambodhi.